Investigation of fungi associated with pet birds and test sensitivity toward fungal antibiotics - Majid Kadhim Abboud AL- Shibli; Ihsan Ali Abdul Redha AL-Zamili (Al-Qadisiyah Journal of Pure Science, 2018)
The current  study  highlighted  the fungi associated with pet birds and the possibility of transmission of these fungi to humans, causing health problems to him, it included a study to isolate and diagnose fungi of pet birds by direct isolation in a manner where the study included four of pet birds are pigeons and love bird  and finches and Canary were unarmed sources are feathers and feed and feces,  the study lasted for six months  For the period from 1 / 10- 01/03/2016  and  included birds in cages houses and shops selling birds in the city of Karbala the study concluded the following:With regard to isolation and diagnosis, the results showed a variation in the number and percentage of fungi isolated depending on the sex of the bird and the source of the isolation was fungus Aspergillus is the most common in birds, where Seen by 59.6% in the love bird and 46% in the Canary and 54% in finches and 71.6% in  the  pigeon , followed by the fungus Penicillium  sp. rates stood at 40.4% in the love bird and 51.3% in the Canary and 44.2% in  finches and 28.4% in the pigeon, followed by the fungus Alternaria sp.  rates stood at 2.70% in the Canary only followed by the fungus Mucor sp. 1.80% in finches only.     With regard to the isolation source has been a source of feathers is the most polluted by fungi where he scored ratios stood at 58.3% and 42.1% and 66.66% and 83.87% for each of the love bird  , Canary, finches, pigeon respectively.The drug allergies isolated fungi from pet birds tested using antibiotics Amphotericin B and Ketoconazole and Fluconazole manner discs has been observed outweigh the clearly antibiotic Ketoconazole against  isolates fungus Aspergillus sp.  where inhibition of 15.6 mm area, 15 mm and 12.6 mm amounted to isolates of feathers , feed  and  feces  respectively while inhibition area of fungus Penicillium sp.  17.6 mm, 15 mm and 15.3 mm for feed and feathers and feces respectively.